Diversity, evenness, & richness of wild mammals along the Sutlej River, Punjab, Pakistan - Sial, Muhammad Amir (Frontiers in Ecology and Evolution, 2024)
Field surveys were conducted at three different water heads—Sulemanki, Islam, and Panjnad—of the Sutlej River from June 2021 to November 2021. This study aimed to estimate the diversity and assess the current threats to the mammalian fauna of the Sutlej River. During the surveys, a total of 266 individuals belonging to four orders, seven families, and twelve different species were observed. The greatest number of individuals belonged to the Rodentia order and the Muridae family. While the lowest number of individuals belonged to the Lagomorpha order and the Leporidae family, both had the same number of individuals. The Panjnad waterhead had the greatest diversity and evenness. The richness of mammals was the same at all three localities. Several threats, such as pollution, habitat destruction, and human−wildlife conflict, which drastically affect mammalian diversity, were observed throughout the investigation.